Exploring the nature, antecedents and consequences of symbolic corporate environmental certification. (15th October 2017) - Martín-de Castro, Gregorio; Amores-Salvadó, Javier; Navas-López, José Emilio; Balarezo-Nuñez, Remy Michael
Abstract: Voluntary environmental certifications can be considered as firms' strategic responses to institutional market and non-market pressures to reduce the impact of business activities on natural environment, and also as a means to legitimate the firm in the eyes of the society and the stakeholders in general, by fitting environmental behaviour to competitive dynamics and strategic choices. Among these certifications, the ISO 14001 is considered as the most widespread environmental management system (EMS) certification. Nevertheless, ISO 14001 cannot disguise the fact that these certifications could be used as a symbolic environmental commitment. In our research, we examine the potential existence of symbolic corporate environmental certification phenomenon, as well as its key antecedents and consequences on firm performance. The proposed hypotheses are tested through a logistic regression and a multiple linear regression on a sample of 157 firms that belong to the Spanish metal production and transformation industry with 100 or more employees. As a result, we found four unexplored antecedents of symbolic corporate environmental certification. While industry technological dynamism and lead cost competitive strategy are negatively related to symbolic corporate environmental certification, certification maturity and product differentiation competitive strategy are positively linked. In addition, contrary to our expectations, the relationship between symbolic corporate certification and firm performance, although present, is not statistically significant. In sum, our research contributes to shed light to the scarcely explored phenomenon of Symbolic Corporate Environmental Certification highlighting its importance in terms of industrial analysis, competitive strategy and timing of adoption, as well as its consequences on firm performance. Highlights: Voluntary environmental certifications as firms' legitimating method. The symbolic character of corporate environmental certifications is highlighted. Four unexplored antecedents of symbolic environmental certification are found. Symbolic corporate environmental certification - firm performance link is analysed.